1985
DOI: 10.1161/01.res.56.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary artery constriction produces a greater right ventricular dynamic afterload than lung microvascular injury in the open chest dog.

Abstract: SUMMARY. Investigators model noncardiogenic pulmonary hypertension by constricting the pulmonary artery to increase right ventricular afterload. To investigate this model's validity, we compared the right ventricular afterload, quantified as pulmonary input impedance, created by constricting the pulmonary artery and by inducing a pulmonary microvascular injury (with glass beads infused into the pulmonary circulation). The pulmonary injury constriction produced a different right ventricular afterload than the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 64 publications
5
37
0
Order By: Relevance
“…Several authors found an increase in Z C during acute PH induced by an abrupt proximal obstruction of the pulmonary arterial tree. This effect mainly results from the reflected waves that come back during systole (before closure of the pulmonary valve) and thus directly oppose blood ejection during ventricular contraction (11,15,16,23,26,39). On the other hand, previous studies of acute PH induced by lung injuries, such as the injection of small (150 -200 m) glass spheres (11,16,23,27), injury with oleic acid (11,29), and during autologous blood clot embolism (23), reported an increase in peripheral resistance, with either stable or decreased Z C .…”
Section: Discussionmentioning
confidence: 99%
“…Several authors found an increase in Z C during acute PH induced by an abrupt proximal obstruction of the pulmonary arterial tree. This effect mainly results from the reflected waves that come back during systole (before closure of the pulmonary valve) and thus directly oppose blood ejection during ventricular contraction (11,15,16,23,26,39). On the other hand, previous studies of acute PH induced by lung injuries, such as the injection of small (150 -200 m) glass spheres (11,16,23,27), injury with oleic acid (11,29), and during autologous blood clot embolism (23), reported an increase in peripheral resistance, with either stable or decreased Z C .…”
Section: Discussionmentioning
confidence: 99%
“…This is in conlrast 10 Ihc finding of Malik , who did not measure any change in PAP and PVR oncc peak levels had been reached [281. Thc reasons for this discrepancy are not c1ear because the experimental settings have basieally been the same (dogs.…”
Section: Catdiovascular Effecis Of Oaigbmentioning
confidence: 72%
“…Thus, the typical elinical symptoms of ARDS [2) were prescnt in our model. The relatively high VofVTof 51% at control see ms 10 be valid: standard techniques have been used for ils detcnnination and similar values have been demonstratcd by others in anesthctized and ventilated dogs as weil as in baboons [11 , 18J. 11 is difficuh to assess to what extent either OA or GB contribuled to the pathological changes in lung funClion. Using l00}.lm GS alone in nonheparinized dogs at a Fi0 2 of 1.0. no diSlurbances of gas exchange have been fou nd in our own pilot experiments.…”
Section: Effeels Ofoaigb On Lung Fllnetionmentioning
confidence: 79%
See 2 more Smart Citations